Assessment of job satisfaction among nursing staff (Journal of Hama University, 2022)
Job satisfaction is the outcome of the interaction between what an individual wants and what he actually gets. It is one of the basic and important components to ensure the proper functioning of any system, especially health systems.So the current descriptive study aimed to assess the level of job satisfaction of the nursing staff. The sample included 301 nurses. The participants were selected by using the convenient sample method. The Minnesota Satisfaction Questionnaire (MSQ) used to measure job satisfaction. Results of study showed that moderate level of general satisfaction for (73.1%) of participants. (65.8%) of participants had a medium level of job satisfaction related to the management domain, (62.5%) of them had a medium level of job satisfaction related to the relationship and that (89.7%) of them had a weak level of job satisfaction related to the salary, and weak at (57.5%) in development opportunities. The study recommends the need of lot increasing attention to financial and supportive incentives for nursing staff members, and seeking to provide educational and training chances to secure opportunities for the development of nursing staff, and conducting other research to determine the most effective factors on the level of job satisfaction.